If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x/3-3/3)+(x/6-1/6)=3
We move all terms to the left:
(2x/3-3/3)+(x/6-1/6)-(3)=0
We can not solve this equation
| 4y−6=6+10y | | 2x+7-4x=24 | | 2u+2=10+3u | | 45-4x=11x | | 21+28x=35+21 | | 2x=51+5x | | 1/3(12x+2)=4x+1-1/3 | | 15s+50=400 | | -6g=-7g+8 | | d+8d+4=4+9d | | 3-2s=-13 | | 3−2s=-13 | | -(-4g+1)=-17 | | 2x+6=7x-16 | | 5(x+3)=2x-10 | | q/4+4=8 | | -9-11x-3x=33 | | q/4+ 4=8 | | 2+5x=6-2x | | x+52+2x-100=180 | | 9h−10=8h | | 102=1.2*c | | 2w−7=1 | | 7x=2x+140 | | 15x2-18x-36=0 | | -3v+3=-7+2v | | 6x+4x=10x | | 25x+3=10x+27 | | X+x=8x-x=6x+x=13x+x=8 | | 3s=1+2s | | 4u-9=3 | | 3+6x=8-3x |